The Impacts of HCl Concentration and Length of Time to Mesocarp in Producing of Bioethanol - M. Amir; Leila Kalsum; Yohandri Bow (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Studies about renewable energy are evolved continuously to decrease the needs of fuel oils that were diminished. One of the alternative energy sources that can be evolved is bioethanol due to the high amount of oxygen component in it hence it can be combustible and eco-friendly. Mesocarp is farming and trading waste of Cocos Nucifera (Coconut) that contains 40% lignin, 44,4% cellulose, and 15% hemicellulose. Delignification is a process of removing lignin from the materials thus it can produce the high purity of cellulose. As long as this, there were numerous studies that researched about lignocellulose biomass, however the least studies researched the impact of using delignification. Thereby, this study was done for figuring out the impact of HCl concentration and length of time to the decreased lignin content and the quality of bioethanol. The points of impacts that being focused on were 1M, 2M, and 3M HCl concentration, whereas the points of length of time impacts were about 60 minutes, 90 minutes, 120 minutes, 150 minutes, and 180 minutes. The decreased lignin content that was obtained is about 18,5% and the finest bioethanol is 97,38 %, 15oC for flash point, 3,8402 cPs for viscosity, and 0,8252 gr/cm3 for density from delignification using 3M HCl for about 150 minutes. Greater HCl concentration to delignification, greater quality of bioethanol that is produced, therefore can be applied to alternative fuel oils for vehicle. Keywords: bioethanol, delignification, HCl, mesocarp